Mapping HA‐tagged protein at the surface of living cells by atomic force microscopy. Issue 1 (23rd December 2014) - Formosa, C.; Lachaize, V.; Galés, C.; Rols, M. P.; Martin‐Yken, H.; François, J. M.; Duval, R. E.; Dague, E.
Abstract : Single‐molecule force spectroscopy using atomic force microscopy (AFM) is more and more used to detect and map receptors, enzymes, adhesins, or any other molecules at the surface of living cells. To be specific, this technique requires antibodies or ligands covalently attached to the AFM tip that can specifically interact with the protein of interest. Unfortunately, specific antibodies are usually lacking (low affinity and specificity) or are expensive to produce (monoclonal antibodies). An alternative strategy is to tag the protein of interest with a peptide that can be recognized with high specificity and affinity with commercially available antibodies. In this context, we chose to work with the human influenza hemagglutinin (HA) tag (YPYDVPDYA) and labeled two proteins: covalently linked cell wall protein 12 (Ccw12) involved in cell wall remodeling in the yeast Saccharomyces cerevisiae and the β2‐adrenergic receptor (β2‐AR), a G protein‐coupled receptor (GPCR) in higher eukaryotes. We first described the interaction between HA antibodies, immobilized on AFM tips, and HA epitopes, immobilized on epoxy glass slides. Using our system, we then investigated the distribution of Ccw12 proteins over the cell surface of the yeast S. cerevisiae . We were able to find the tagged protein on the surface of mating yeasts, at the tip of the mating projections. Finally, we could unfold multimers of β2‐AR from the membrane of living transfected chinese hamster ovary cells. This result is in agreement with GPCR oligomerization in living cell membranes and opens the door to the study of the influence of GPCR ligands on the oligomerization process. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : We first described the interaction between hemagglutinin (HA) antibodies, immobilized on atomic force microscopy tips, and HA epitopes, immobilized on epoxy glass slides (model surface). Using our system, we then investigated the distribution of HA‐labeled yeast cell wall protein covalently linked cell wall protein 12 over the cell surface of the yeast Saccharomyces cerevisiae during mating process. Finally, we could unfold multimers of HA‐labeled β2‐adrenergic receptors from the membrane of living transfected Chinese hamster ovary cells.